2006
DOI: 10.1136/sti.2006.023366
|View full text |Cite
|
Sign up to set email alerts
|

Violence against wives, sexual risk and sexually transmitted infection among Bangladeshi men

Abstract: Objective: To assess the relationship between men's reported violence against wives and their sexual risk behaviours and sexual health. Design, setting and participants: Cross-sectional analyses of a survey of a nationally representative household-based sample of married men in Bangladesh (n = 3096). Main outcome measure(s): Physical and sexual violence against wives during the previous 12 months was assessed and examined for relations to men's extramarital sexual behaviours and sexually transmitted infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 31 publications
9
96
1
3
Order By: Relevance
“…Separate hierarchical linear multiple regression analyses tested each model. Based on previous research on IPV perpetration, 42,43 demographics (age, education, and public assistance) and relationship characteristics (cohabitation and relationship length) were entered as covariates in the first and second steps of each model. The predictor variable (attitudes supporting IPV) was entered into the second step, and each moderator variable (ineffective couple conflict resolution communication and neighborhood violence) was entered into the third step of its model.…”
Section: Data Analysis Planmentioning
confidence: 99%
“…Separate hierarchical linear multiple regression analyses tested each model. Based on previous research on IPV perpetration, 42,43 demographics (age, education, and public assistance) and relationship characteristics (cohabitation and relationship length) were entered as covariates in the first and second steps of each model. The predictor variable (attitudes supporting IPV) was entered into the second step, and each moderator variable (ineffective couple conflict resolution communication and neighborhood violence) was entered into the third step of its model.…”
Section: Data Analysis Planmentioning
confidence: 99%
“…Abusive men are more likely to engage in high-risk behaviours that increase not only the likelihood of their acquisition of STI, but also that they infect their female partners (1,13,15,16). A study among 428 men reporting multiple sexual partners, in Cape Town, South Africa, found men's report of STI symptoms and engagement in transactional sex were associated with their perpetration of physical and sexual partner violence, and alcohol consumption or substance abuse and inconsistent condom use were associated with their perpetration of physical partner violence (15).…”
Section: Pathways To Sti Riskmentioning
confidence: 99%
“…Existence of such a problem is not unlikely in Bangladesh [12]. Scientists have tried to relate violence by intimate partner with different social facets, but the influence of violence by male partners on unintended pregnancy in female partner has not been delved elaborately.…”
Section: Proble M Statementmentioning
confidence: 99%
“…In South Asia, considerable prevalence of most forms of violence have been indicated over the last decade [10][11][12].…”
Section: Introductionmentioning
confidence: 99%